Microfluidic chip for isolation of viable circulating tumor cells of hepatocellular carcinoma for their culture and drug sensitivity assay - Zhang, Yu; Zhang, Xiaofeng; Zhang, Jinling; Sun, Bin; Zheng, Lulu; Li, Jun; Liu, Sixiu; Sui, Guodong; Yin, Zhengfeng (Cancer biology & therapy, 2016)
Circulating tumor cells (CTCs) have been proposed to be an active source of metastasis or recurrence of hepatocellular carcinoma (HCC). The enumeration and characterization of CTCs has important clinical significance in recurrence prediction and treatment monitoring in HCC patients. We previously developed a unique method to separate HCC CTCs based on the interaction of the asialoglycoprotein receptor (ASGPR) expressed on their membranes with its ligand. The current study applied the ligand-receptor binding assay to a CTC-chip in a microfluidic device. Efficient capture of HCC CTCs originates from the small dimensions of microfluidic channels and enhanced local topographic interactions between the microfluidic channel and extracellular extensions. With the optimized conditions, a capture yield reached > 85% for artificial CTC blood samples. Clinical utility of the system was further validated. CTCs were detected in all the examined 36 patients with HCC, with an average of 14 ± 10/2 mL. On the contrary, no CTCs were detected in healthy, benign liver disease or non-HCC cancer subjects. The current study also successfully demonstrated that the captured CTCs on our CTC-chip were readily released with ethylene diamine tetraacetic acid (EDTA); released CTCs remained alive and could be expanded to form a spheroid-like structure in a 3-dimensional cell culture assay; furthermore, sensitivity of released CTCs to chemotherapeutic agents (sorafenib or oxaliplatin) could be effectively tested utilizing this culture assay. In conclusion, the methodologies presented here offer great promise for accurate enumeration and easy release of captured CTCs, and released CTCs could be cultured for further functional studies.